Unveiling the health implications of working hours in the Indonesian workforce - Wicaksono, Padang; Akbar, Poeti Nazura Gulfira; Wienartha, Della Anissa (International Journal of Innovative Research and Scientific Studies, 2024)
This research aims to evaluate and compare the impact of working hours on the physical and psychological well-being of workers before and during the COVID-19 pandemic, where people were forced to work from home. While existing studies primarily concentrate on the physical and mental health of office workers, there is a notable gap in understanding how changes in work hours affect individuals in various professional sectors. This study seeks to address this gap by conducting a comprehensive investigation across a diverse range of employment, encompassing white collar, gray collar, and blue collar occupations. Using datasets from Indonesia’s National Labor Survey (Sakernas) in 2019 and 2020, the study focuses on the working-age population engaged in various occupations, including employees, casual agricultural workers, and casual non-agricultural workers. Further categorization involves classifying individuals into white collar, gray collar, and blue collar segments. The total number of individuals analyzed was 215,607 in 2019 and 201,077 in 2020. Employing an ordered logistic regression method due to the categorical nature of the dependent variable, the study reveals consistent findings regarding the impact of working hours on health across the years 2019 and 2020. Extended work hours correlate with improved health outcomes, indicating better health for those working longer, while individuals with fewer hours exhibit lower chances of achieving good health. In 2019, occupational status significantly influences worker health, with gray and blue collar workers having lower probabilities of better health compared to white collar workers. However, this occupational effect on health is absent in 2020.